Tinjauan Kritis Terhadap Peraturan Mahkamah Agung Nomor 2 Tahun 2012 Tentang Batasan Tindak Pidana Ringan dan Jumlah Denda dalam KUHP - Tahir, Ach (UIN Sunan Kalijaga Yogyakarta, 2012)
Justice is one of the purposes of any legal system, even the most important is mygoal. There are still other legal purposes is also always the purpose of the law, namelyjustice, rule of law, expediency, and order. However, from the fourth grade, according tothe Greek philosopher, Plato, justice is the highest virtue. According to Plato justice is